2012
DOI: 10.1007/s10714-012-1392-x
|View full text |Cite
|
Sign up to set email alerts
|

On coincidence problem in ELKO dark energy model

Abstract: We study the critical points of a universe dominated by ELKO spinor field dark energy and a barotropic matter without considering a specific potential or interaction. The coincidence problem and attractor solutions are discussed at late time, and it is shown that the coincidence problem can not be solved in this model. PACS numbers: 95.36.+x, 95.35.+d, 98.80.-k * mohsenisad@ut.ac.ir

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 36 publications
0
35
0
Order By: Relevance
“…Since recent works [65][66][67][68] have not found stable points for such system for different dynamic variables and interactions terms, we are led to believe (without demonstration) that the system ELKO-DM does not allow stable points. Based on these results, we have supposed there to be an additional constraint to the dynamical system, namely that the potential of the ELKO field is related to a constant parameter δ; then we have analyzed the stability conditions for such a new system.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Since recent works [65][66][67][68] have not found stable points for such system for different dynamic variables and interactions terms, we are led to believe (without demonstration) that the system ELKO-DM does not allow stable points. Based on these results, we have supposed there to be an additional constraint to the dynamical system, namely that the potential of the ELKO field is related to a constant parameter δ; then we have analyzed the stability conditions for such a new system.…”
Section: Discussionmentioning
confidence: 89%
“…Such a search for adequate variables depends in general on the structure of the physical quantities involved, like the energy density, pressure and Friedmann constraints. In some recent works [65][66][67], different choices of variables for interacting systems concerning the ELKO field have shown that there are no stable points in order to explain the cosmic coincidence problem. In [68] a new method of analysis was proposed, based on a constant parameter that leads to stable points under some conditions.…”
Section: Introductionmentioning
confidence: 99%
“…[3]. These formulations boosted several works in a broad range of areas, for instance mathematical physics [4][5][6][7][8][9][10], phenomenology of particles [11][12][13][14][15][16] and cosmology [17][18][19][20][21][22][23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Several cosmological applications of this new field have been done, first in torsion free frameworks [10][11][12][13][14][15][16][17][18][19] and more recently considering its coupling to torsion [20][21][22][23] in an Einstein-Cartan framework, which turns the system of equations richer than the previous case, especially for inflationary applications. In particular, in Refs.…”
Section: Introductionmentioning
confidence: 99%